2003
DOI: 10.1002/ajh.10411
|View full text |Cite
|
Sign up to set email alerts
|

Sickle cell patient with an acute chest syndrome and a negative chest X‐ray: Potential role of the ventilation and perfusion (V/Q) lung scan

Abstract: Acute chest syndrome (ACS) in sickle cell disease is caused by thromboemboli in the pulmonary vasculature. The diagnostic criteria include the presence of pulmonary infiltrate(s) on chest x-ray. This case report suggests that a V/Q scan may play a diagnostic role in sickle cell patients with symptoms of ACS and a negative chest x-ray. Am.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Those admitted to this study fulfilled two criteria at presentation or on previous episodes: (a) new infiltrate on chest radiograph (X-ray) and (b) new respiratory symptom or sign mainly chest pain, cough, wheezing, tachypnea and/or fever (>38.5°C). Although it is reported that rare cases of ACS presented with normal chest X-ray,[19] but still the selected criteria is keeping with the most widely accepted definition of ACS. [6] Historical data, clinical features, CBC (using automated counter), Hb-electrophoresis (using sickling test and alkaline ± acid gel-electrophoresis methods), G6PD activity (using fluorescent screening test), Cultures (whenever needed), radiological studies such as; plain chest X-ray; abdominal ultrasound (measurement of splenic long axis length and evaluation of hepatobiliary tree), room air arterial blood gases (were done on admission whenever possible), blood transfusion rate/year, hospitalization rate, severity status (average number of acute admission / year for crisis, ACS, priapism, stroke, etc.…”
Section: Methodsmentioning
confidence: 99%
“…Those admitted to this study fulfilled two criteria at presentation or on previous episodes: (a) new infiltrate on chest radiograph (X-ray) and (b) new respiratory symptom or sign mainly chest pain, cough, wheezing, tachypnea and/or fever (>38.5°C). Although it is reported that rare cases of ACS presented with normal chest X-ray,[19] but still the selected criteria is keeping with the most widely accepted definition of ACS. [6] Historical data, clinical features, CBC (using automated counter), Hb-electrophoresis (using sickling test and alkaline ± acid gel-electrophoresis methods), G6PD activity (using fluorescent screening test), Cultures (whenever needed), radiological studies such as; plain chest X-ray; abdominal ultrasound (measurement of splenic long axis length and evaluation of hepatobiliary tree), room air arterial blood gases (were done on admission whenever possible), blood transfusion rate/year, hospitalization rate, severity status (average number of acute admission / year for crisis, ACS, priapism, stroke, etc.…”
Section: Methodsmentioning
confidence: 99%
“…This usually reveals widespread perfusion defects with normal ventilation (Noto, ; Feldman et al , ; Kaur et al , ). However, the appearances may be confused with pulmonary emboli or diminished by the presence of other pathology, such as pleural effusions.…”
Section: Monitoring and Investigationsmentioning
confidence: 99%
“…We believe that a combination of vasoocclusion and increased marrow blood flow is adequate to dislodge necrotic marrow material into the circulation. A ventilation and perfusion scan may be useful when this is initially suspected [87]. Once a vaso-occlusive crisis develops, the ensuing hypoxia and tissue hypoxemia cause sickling of erythrocytes.…”
Section: Review Of Literaturementioning
confidence: 99%